A case of Becker myotonia with pseudodominant inheritance: сurrent approaches to the differential diagnosis of Thomsen’s and Becker's myotonia congenita - S. A. Kurbatov; S. S. Nikitin; S. N. Illarioshkin; P. Gundorova; A. V. Polyakov (Нервно-мышечные болезни)
Myotonia congenital (MC) is the most common form of the hereditary nondystrophic myotonias caused by mutations in the skeletal muscle chloride channel gene (CLCN1) which change the functional features of muscle fibers membrane. MC is represented by two allelic forms with different types of inheritance: Thomsen’s myotonia congenita (TMC) with an autosomal dominant and Becker’s myotonia congenita (BMC) with an autosomal recessive inheritance. Both forms, TMC and BMC have the same clinical manifestation: skeletal muscle hypertrophy, transient weakness, generalized myotonia, debut in early childhood and a stationary development. Diseases are characterized by equal neurophysiological changes. In the family usually only one patient is detected. In some cases with the horizontal segregation diseases, more than one mutation in CLCN1 gene is found. These factors complicate the diagnosis of TMC and BMC, further medical and genetic counseling of the family members even after the patient’s genotype is detected. The confirmed BMC case with pseudo dominant type of inheritance and limited clinical manifestation is discussed in the light of differential diagnosis of the two discussed diseases.